Investigation of the Effect of Coating Light Steel Container Houses with Nano-TiO2 on Dynamic Parameters Using OMA - Furkan Günday (Buildings)
In recent years, the integration of nano titanium dioxide (TiO2) into building materials has become a popular research topic due to its superior mechanical, photocatalytic and self-cleaning properties. In this study, the dynamic behavior of a light steel container house model coated with nano-TiO2 is investigated using Operational Modal Analysis (OMA). The effects of TiO2 on the natural frequencies, damping ratios and mode shapes of the light steel container house model are investigated. The Stochastic Subspace Identification-Unweighted Principal Component (SSI-UPC) method is used to extract the modal parameters from the ambient vibration data. The results show that the TiO2 coating significantly increases the stiffness and improves the damping properties by increasing the natural frequencies of the light steel container house model. The findings indicate that nano-TiO2 coatings can increase the structural integrity and durability of light steel container houses. This study provides a foundation for future research on nano-reinforced coatings in light steel structural systems.